The Impact of Voluntary Accounting Disclosure in the Financial Reports to Rationalize the Investors Decisions in Industrial Companies Listed in the Amman Stock Exchange - Al-Theebeh, Ziad Abdel Halim; Jodeh, Ibraheem N. M.; Mahmood, Hasan Tawfiq; Khaled, Hazem (International Journal of Economics and Financial Issues, 2018)
The objective of this study was to identify the effect of the voluntary accounting disclosure in the financial reports on the rationalization of the decisions of investors in the industrial companies listed In the Amman Stock Exchange, and to identify the most important provisions of the voluntary accounting disclosure impact on investor decisions. This study adopted the analytical descriptive approach, one of the main findings of the study that the voluntary accounting disclosures clearly affect the rationalization of the decisions of investors in the industrial companies listed in the Amman Stock Exchange, be it investment decision, sale or retention. Among the most important recommendations suggested by the study is: the interest in publishing voluntary accounting information, which helps to rationalize investors’ decisions, by publishing summaries attached to the financial statements. Keywords: Voluntary Accounting Disclosure, Rationalize the Investors Decisions, Industrial Companies. JEL Classification: M4